Stochastic Variation in Expression of the Tricarboxylic Acid Cycle Produces Persister Cells - Eliza A. Zalis; Austin S. Nuxoll; Sylvie Manuse; Geremy Clair; Lauren C. Radlinski; Brian P. Conlon; Joshua Adkins; Kim Lewis (mBio, 2019)
ABSTRACT Chronic bacterial infections are difficult to eradicate, though they are caused primarily by drug-susceptible pathogens. Antibiotic-tolerant persisters largely account for this paradox. In spite of their significance in the recalcitrance of chronic infections, the mechanism of persister formation is poorly understood. We previously reported that a decrease in ATP levels leads to drug tolerance in Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. We reasoned that stochastic fluctuation in the expression of tricarboxylic acid (TCA) cycle enzymes can produce cells with low energy levels. S. aureus knockouts in glutamate dehydrogenase, 2-oxoketoglutarate dehydrogenase, succinyl coenzyme A (CoA) synthetase, and fumarase have low ATP levels and exhibit increased tolerance of fluoroquinolone, aminoglycoside, and β-lactam antibiotics. Fluorescence-activated cell sorter (FACS) analysis of TCA genes shows a broad Gaussian distribution in a population, with differences of over 3 orders of magnitude in the levels of expression between individual cells. Sorted cells with low levels of TCA enzyme expression have an increased tolerance of antibiotic treatment. These findings suggest that fluctuations in the levels of expression of energy-generating components serve as a mechanism of persister formation. IMPORTANCE Persister cells are rare phenotypic variants that are able to survive antibiotic treatment. Unlike resistant bacteria, which have specific mechanisms to prevent antibiotics from binding to their targets, persisters evade antibiotic killing by entering a tolerant nongrowing state. Persisters have been implicated in chronic infections in multiple species, and growing evidence suggests that persister cells are responsible for many cases of antibiotic treatment failure. New antibiotic treatment strategies aim to kill tolerant persister cells more effectively, but the mechanism of tolerance has remained unclear until now.